2012
DOI: 10.3329/jesnr.v5i1.11550
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic and Antihyperlipidemic of Karala (Momordica charantia) Fruits in Streptozotocin Induced Diabetic Rats

Abstract: To investigate the antihyperglycemic and antihyperlipidemic effect of Momordica charantia (Karala), the aqueous extract of the Karala fruit was tested on streptozotocin (STZ)-induced diabetic rats. Thirty six albino rats were used in the experiment, 30 diabetic and the remaining six as negative control (T1). Diabetes was induced by administering (injecting) STZ at dose of 55mg/kg body weight. Thirty diabetic animals were randomly divided into five groups such as diabetic control group (T2) without any applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Shetty et al [ 25 ] also found a marginal increase in body weight of diabetic rats fed with diet containing bitter gourd. Similar findings by Hossain et al [ 27 ] also strengthen the current results that body weight of diabetic groups treated with bitter gourd was higher than the untreated diabetic group.
Fig.
…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Shetty et al [ 25 ] also found a marginal increase in body weight of diabetic rats fed with diet containing bitter gourd. Similar findings by Hossain et al [ 27 ] also strengthen the current results that body weight of diabetic groups treated with bitter gourd was higher than the untreated diabetic group.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…Serum creatinine and urea concentration was also remained in normal ranges due to feeding of bitter gourd in diet. The current data is comparable to the earlier investigations of Hossain et al [ 27 ] confirmed a reduction in serum ALP, ALT and AST of rats treated with bitter gourd extract. In another study noted that bitter gourd is helpful in reducing the amount of ALT and AST.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Examples of such studies are: Akter, Mahabub-Uz-Zaman, and Rahman, 2013; Al-Amin, Uddin, Rizwan, and Islam, 2013; Ali et al, 1993; Amran, Sultan, Rahman, and Rashid, 2013; Bhuyan, Rokeya, Masum, Hossain, and Mahmud, 2010; Borhanuddin, Shamsuzzoha, and Hussain, 1994b; A. Chowdhury and Biswas, 2012; A. R. Das, Mostofa, Hoque, Das, and Sarkar, 2010; Habib and Gafur, 2003; J. M. A. Hannan et al, 2003; E. Haque, Saha, Islam, and Islam, 2012; M. A. Hossain et al, 2012; Md Alamgir Hossain, Roy, Ahmed, Chowdhury, and Rashid, 2007b; M. Z. Hossain, Shibib, and Rahman, 1992; Islam et al, 2009; M. A. Islam et al, 2011; I. A. Jahan et al, 2009; Mostofa et al, 2007b; Mowl, Alauddin, Rahman, and Ahmed, 2009; Rafiq, Sherajee, Nishiyama, Sufiun, and Mostofa, 2009; Md Masudur Rahman, Hossain, Siddique, Biplab, and Uddin, 2012b; Md Mahfuzur Rahman, Sayeed, Haque, Hassan, and Islam, 2012; M. W. Rahman et al, 2005; Rokeya, Bhowmik, Khan, and Khter, 2009; M. G. Roy et al, 2010; Shahreen et al, 2012; Shibib, Khan, and Rahman, 1993; Sikder, Kaisar, Rahman, Hussain, and Rashid, 2011; Talukder, Khan, Uddin, Jahan, and Alam, 2012; Urmi et al, 2012; Zulfiker et al, 2011 [ 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 ]. These scientific studies emphasized the correlation among traditional use and the pharmacological properties of antidiabetic plants.…”
Section: Phytochemical and Experimental Studies Of Antidiabetic Plants In Bangladeshmentioning
confidence: 99%
“…Hence, in the current study the aqueous extracts of M. charantia friuts, were estimated for the potential anti hyperlipidemic and antidiabetic effect on streptozotocin -induced diabetic rats and compared with the result with glibenclamide, a standard antidiabetic medicine [22]. The hypoglycemic probable mechanisms in M. charantiahave been recognized as glycosides, triterpenes, polysaccharides, saponins, alkaloids, steroids and proteins.…”
Section: Anti -Diabetic Propertiesmentioning
confidence: 99%